The Models of Constitutional Interpretation between the Constitutional Court of Indonesia and Japan: The Case of the Verdict Regarding Illegitimate Child - Rudy Rudy (Faculty of Law, Universitas Padjadjaran, 2014)
AbstractThe Constitutional Court of Indonesia issued a landmark judgment on February 2012 stipulating that the civil rights of children born out of wedlock should be recognized by their biological fathers. In June 2008, the Supreme Court of Japan issued a judgment that struck down the same issue stipulating that illegitimate child shall be acknowledged as having legal relationship with the father, and that the Nationality Act was violation of the constitution. These two judgments call comparative study on constitutional judgment and interpretation. In the specific area of constitutional interpretation, Vicki C. Jackson has argued that at least three models might broadly describe the relationships between domestic constitutions and law from trans-national sources. Firstly, the convergence model that assumes the desirability of convergence with the constitutional laws of other nations; secondly, the resistance model that relishes resistance by national constitutions from foreign influence; and the engagement model arguing that the constitution can best be viewed as a site of engagement with the trans-national, informed but not controlled by legal norms of other nations and questions they put to interpret their constitution. Based on the theory, the aim of this article is to see the models of interpretation of constitutional relationships between Indonesia and Japan while both nations give similar judgments on illegitimate child. This study will answer this question by integrating the interpretation of the judgments of The Constitutional Court of Indonesia and the Supreme Court of Japan on illegitimate Child. Hopefully, the result of this research paper may enlighten the context of constitutionalism in Asia.Keywords: comparative, constitutionalism, engagement, illegitimate child, judgment. Model Interpretasi Konstitusi di Indonesia dan Jepang: Tinjauan Kasus mengenai Putusan Anak yang Lahir di Luar NikahAbstrakPada Februari 2012, Mahkamah Konstitusi Indonesia memberikan putusan yang bersejarah yang mengatur hak perdata setiap anak yang lahir di luar nikah agar diakui oleh ayah biologisnya. Pada Juni 2008, Mahkamah Agung Jepang mengeluarkan putusan yang membatalkan permasalahan yang sama terhadap klausa dalam undang-undang nasional sebagai suatu pelanggaran atas konstitusi yang mengatur bahwa anak yang lahir di luar nikah harus diakui memiliki hubungan resmi dengan ayah biologisnya. Kedua putusan ini memberikan studi komparatif dalam hal putusan konstitusi dan penafsirannya. Di dalam area spesifik mengenai penafsiran konstitusi, Vicki C. Jackson telah memberikan argumentasi bahwa sedikitnya terdapat tiga bentuk yang dapat menggambarkan hubungan antara konstitusi dalam negeri dan hukum dari sumber yang transnasional, yaitu: bentuk campuran yang menunjukkan adanya keinginan untuk mencampurkan hukum konstitusi nasional dengan negara lain; bentuk penolakan adanya pengaruh luar terhadap konstitusi nasional; dan bentuk penerimaan yang berpendapat bahwa konstitusi lebih baik dilibatkan secara transnasional, mengetahui tetapi tidak terpengaruh oleh pertimbangan norma hukum negara lain dan terhadap pertanyaan yang mereka ajukan mengenai konstitusi nasional secara spesifik. Dalam teori ini, penulisan ini bertujuan untuk mengetahui bentuk dari penafsiran hubungan konstitusi antara Indonesia dan Jepang sebagaimana kedua negara tersebut telah memberikan putusan dalam kasus anak yang lahir di luar nikah. Penulisan ini bertujuan untuk menjawab pertanyaan dengan meningkatkan pembacaan atas putusan Mahkamah Konstitusi Indonesia dan putusan Mahkamah Agung Jepang dalam kasus anak yang lahir di luar nikah. Semoga hasil dari penulisan penelitian ini dapat memberikan pencerahan terhadap konstitusionalisme di Asia.Kata Kunci: anak yang lahir di luar nikah, hubungan, konstitusionalisme, perbandingan, putusan. DOI: https://doi.org/10.22304/pjih.v1n1.a9